Cardiac Imaging for Risk Assessment of Malignant Ventricular Arrhythmias in Patients With Mitral Valve Prolapse - Tayal, Bhupendar; Delling, Francesca N.; Malahfji, Maan; Shah, Dipan J. (Frontiers in Cardiovascular Medicine, 2021)
Recent studies have described the occurrence of complex ventricular arrhythmias and sudden cardiac death among patients with mitral valve prolapse (MVP). The reported incidence rate of sudden cardiac death or ventricular tachycardia is about 1–1.5% among patients with MVP. Various imaging markers have been associated with this increased risk, including mitral annular disjunction, replacement fibrosis by late gadolinium enhancement, and mechanical dispersion. In this review, we briefly discuss how multimodality cardiac imaging can be applied to identify MVP patients with high risk of sudden cardiac death and complex ventricular arrhythmias.